2019
DOI: 10.1016/j.apradiso.2019.108873
|View full text |Cite
|
Sign up to set email alerts
|

Radiosynthesis of carbon-11 labeled PDE5 inhibitors as new potential PET radiotracers for imaging of Alzheimer's disease

Abstract: To develop PET tracers for imaging of Alzheimer's disease, new carbon-11 labeled potent and selective PDE5 inhibitors have been synthesized. The reference standards (5) and (12), and their corresponding desmethylated precursors (6) and (13) were synthesized from methyl 2-amino-5bromobenzoate and (4-methoxyphenyl)methanamine in multiple steps with 2%, 1%, 1% and 0.2% overall chemical yield, respectively. The radiotracers ([ 11 C]5) and ([ 11 C]12) were prepared from their corresponding precursors 6 and 13 with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Interestingly, highest radiochemical yields for automated radiosynthesis of [ 18 F]17 were achieved by using the nosylate precursor and [ 18 F]TBAF with the addition of small amounts of water to the reaction mixture [73]. 4) have been published by collaborating research groups from Hebei, China, and Indiana, USA [75,77]. Dong et al [75] focused on the PDE5 enzyme as a promising non-beta amyloid-related target for treatment and imaging of Alzheimer´s disease and thus, [ 11 C]19 and [ 11 C]20 were generated to investigate PDE5 in the brain by PET.…”
Section: Pde5 Radioligandsmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, highest radiochemical yields for automated radiosynthesis of [ 18 F]17 were achieved by using the nosylate precursor and [ 18 F]TBAF with the addition of small amounts of water to the reaction mixture [73]. 4) have been published by collaborating research groups from Hebei, China, and Indiana, USA [75,77]. Dong et al [75] focused on the PDE5 enzyme as a promising non-beta amyloid-related target for treatment and imaging of Alzheimer´s disease and thus, [ 11 C]19 and [ 11 C]20 were generated to investigate PDE5 in the brain by PET.…”
Section: Pde5 Radioligandsmentioning
confidence: 99%
“…For that purpose, radioligands with subnanomolar potency and high target selectivity are required as mentioned above. Out of a series of novel naphthyridine and 1H-pyrroloquinolinone analogs [75,82], the most potent candidates 19 and 20 displayed picomolar inhibitory potency towards PDE5 and excellent selectivity over PDE6 (Figure 4), which shows high similarity in the catalytic site with PDE5 [82]. Besides, Xu et al [77] reported on the development of [ 11 C]21 for PET imaging of PDE5 in the heart.…”
Section: Pde5 Radioligandsmentioning
confidence: 99%
See 2 more Smart Citations
“…The latest PDE5-targeting radiotracers, quinolines 10 and 11 , and 4(3 H )-pyrimidinone 12 , have been developed as high-potency PET tracers (IC 50 = 0.056, 0.059, 0.62 nM, respectively) for imaging PDE5 in AD and heart disease, although their use in animal or tissue studies has yet to be reported. 27 , 28 …”
Section: Introductionmentioning
confidence: 99%